Comparative investigation of carbon fiber filaments in off-axis transverse cutting between flexible-support and non-support method under pre-tension. (March 2019) - Chen, Yang; Lu, Longsheng; Liu, Xiaokang; Xie, Yingxi; Wan, Zhenping; Hou, Zhaorui
Short carbon fiber is an effective and essential reinforced material in composite domains. Generally, it is produced by chopping technology, among which pressing roller and grooved wheel are two popular chopping techniques. According to the working principle of these two techniques, the pressing roller can be simplified as a flexible-support cutting in off-axis transverse cutting, meanwhile the grooved wheel can be represented by a non-support cutting. To reveal the fracture difference of carbon fiber between the pressing roller and the grooved wheel technique, comparative investigation of failure behavior between a single carbon fiber (also simplified as a filament) with flexible support and with non-support was performed in off-axis transverse cutting using a custom-designed fixture. Both the cutting force and the fracture surface of the filament were comparatively analyzed in cutting process. It was found that the failure of single carbon fiber was caused by tensile effect in a non-support cutting, whereas that in a flexible-support cutting was caused by bending effect. The cutting-off force and cutting-off depth of filament cut by use flexible support are significantly lower than that by use non-support under low pre-tension. It is interesting to find out that the failure spot of carbon fiber filament in non-support cutting under low pre-tension tends to occur randomly. Meanwhile, in a flexible-support cutting, the break point of carbon fiber filament is determined by the tip of the blade. After a comprehensive comparison, the flexible-support cutting is a prior selection to produce short carbon fibers compared with the non-support cutting.